2014
DOI: 10.1007/s00381-014-2435-2
|View full text |Cite
|
Sign up to set email alerts
|

The value of transcranial Doppler imaging in children with tuberculous meningitis

Abstract: Purpose Transcranial Doppler imaging (TCDI) is potentially a valuable investigational tool in children with tuberculous meningitis (TBM), a condition often complicated by pathology relevant to Doppler imaging such as raised intracranial pressure (ICP) and cerebral vasculopathies. Methods Serial TCDI was performed on 20 TBM children with the aim of investigating cerebrovascular haemodynamics and the relationship between pulsatility index (PI) and ICP. Results We observed a poor correlation between ICP and PI in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 22 publications
2
36
1
Order By: Relevance
“…This is invasive and only possible during intensive care admission in settings where such facilities exist. Transcranial Doppler [46] and near-infrared spectroscopy provide less-invasive alternatives, but these methods require more rigorous validation and have not yet demonstrated clinical utility. Simple measures to reduce cerebral ischemia and brain cell metabolic stress include maintaining adequate blood pressure and glucose levels, providing supplemental oxygen, and controlling fever [47].…”
Section: Management and Monitoringmentioning
confidence: 99%
“…This is invasive and only possible during intensive care admission in settings where such facilities exist. Transcranial Doppler [46] and near-infrared spectroscopy provide less-invasive alternatives, but these methods require more rigorous validation and have not yet demonstrated clinical utility. Simple measures to reduce cerebral ischemia and brain cell metabolic stress include maintaining adequate blood pressure and glucose levels, providing supplemental oxygen, and controlling fever [47].…”
Section: Management and Monitoringmentioning
confidence: 99%
“…These findings are similar to those we demonstrated in a recent study, which compared the transcranial Doppler-derived PI and cerebrospinal fluid opening pressure after lumbar puncture. 5 We also found that a PI of 1.26 or higher was predictive of opening pressures of 20 cm H 2 O or higher (sensitivity, specificity, positive predictive value, negative predictive value, and overall accuracy were 81.1%, 96.3%, 93.8%, 88.1%, and 90.1%, respectively). Although we share the authors' optimism that transcranial Doppler sonography has potential as a monitoring tool in patients with suspected raised intracranial pressure, we wish to highlight some of the factors that may influence transcranial Doppler-derived flow dynamics and how they may affect the design of future studies and possible applications in the field.…”
Section: Transcranial Doppler Sonography In Patients With Severe Braimentioning
confidence: 51%
“…We demonstrated that potential in our recent study, in which we followed the progress of 2 patients with raised intracranial pressure secondary to meningitis and encephalitis. 5 In both cases, changes in intracranial pressure were reflected by changes in the transcranial Doppler-derived PI, yet other patients in the study with similar intracranial pressure measurements had different PI values. In another patient with sinus thrombosis, we also observed a fall in the PI over several weeks, in association with resolution of papilloedema.…”
Section: Transcranial Doppler Sonography In Patients With Severe Braimentioning
confidence: 75%
“…used TCD to study blood flow velocities and found high velocities in basal cerebral arteries in 14 children diagnosed with TBM. 7 These high values persisted for 7 days suggesting the cause of elevated velocities to be vasculitis rather than functional vasospasm. Further, in children with non-communicating hydrocephalus, a decline in PI values was noted post CSF diversion procedure.…”
Section: Discussionmentioning
confidence: 98%